منهج ابن تيمية في الرد على الأشاعرة من خلال كتابه ( درء تعارض العقل والنقل ) - جدي، محمد مصطفى (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
This study aims to examine Imam Ibn Taymiyyah's dialectical Manhaj (methodology) which he used to respond to the Ash'arites on disputed issues through his perspectives in his book, “Dar' al-' ta'aruḍ bayan al-Naql wa al-'Aql .” The study attempts to answer this main question, what are the features of Ibn Taymiyyah's Manhaj in responding to the Ash'arites?' The researcher first discussed briefly Ibn Taymiyyah's biography, the factors that contributed to his knowledge construction, and then presented details of his book. The nature of Ibn Taymiyyah's Manhaj, its importance in Aqidah studies, the principles of Aqidah Manhaj of the Ash'arites and the developmental stages of their Manhaj were also thoroughly discussed. Meanwhile, the study focused on Ibn Taymiyyah's methodological principles in dealing with the Ash'arites, their resources and ways of writing, reasoning the issues of belief, and responding to intellectual dissents/disagreements. Each principle within their cotent was discussed in detailed. Most importantly, the study found that Ibn Taymiyyah was positive towards the Ash'arites, and did justice to them on the disputed issues. He utilized very clear methodology in his book, “Dar' al-' ta'aruḍ bayan al-Naql wa al-'Aql , ” in both the formulation of ideas and his response to disputants such as identifying their mistakes in the given evidences and replacing them with corrected ones as he believed, through various ways of criticism, narration and documentation. However, he disagreed with the Ash'arites on the issue of Ta'wil (Interpretation). The study ended with some recommendations that could be useful for further studies on Ibn Taymiyyah's method in responding to the Ash'arites and other topics related to his personality.